Statistics of public expenditure for economic development (SPEED) 2010 [Archived version] - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
In many developing countries, weak institutions and fiscal mismanagement often lead to poor access and weak delivery of public services, such as health, education, and basic infrastructure. Improving the efficiency of public spending is an important economic and political tool, along with good governance and a strong revenue stream, for improved public sector management. An efficient public sector serves an important role in a country 's economic development by promoting adequate and appropriate allocation of resources. Even small steps toward prudent fiscal management can benefit the poor and other disadvantaged groups by allowing the provision of effective and targeted public services. A better understanding of the linkages between public expenditure and development can provide insights for poverty reduction strategies and key development goals. With this objective, IFPRI has compiled the Statistics of Public Expenditure for Economic Development (SPEED) database, providing the most comprehensive and publicly available public expenditure information for 67 countries and six sectors: agriculture, education, health, defense, social protection, and transportation and communication, for the time period 1980-2007. The SPEED database is available for use by researchers, policymakers, donors, and others in the development community for a variety of economic and policy applications.